Recurrent Skin and Lung Infections in Autosomal Dominant Hyper IgE Syndrome with Transactivation Domain STAT3 Mutation - Chad J. Cooper; Sarmad Said; German T. Hernandez (Case Reports in Immunology)
Background. Hyper IgE is a rare systemic disease characterized by the clinical triad of high serum levels of IgE (>2000 IU/mL), eczema, and recurrent staphylococcal skin and lung infections. The presentation of hyper IgE syndrome is highly variable, which makes it easy to confuse the diagnosis with that of severe atopy or other rare immunodeficiency disorders. Case Report. A 23-year-old Hispanic presented with history of frequent respiratory and gastrointestinal infections as a child and multiple episodes of skin and lung infections (abscess) with Staphylococcus aureus throughout his adult life. He had multiple eczematous lesions and folliculitis over his entire body, oral/esophageal candidiasis, and retention of his primary teeth. The IgE was elevated (>5000 IU/mL). Genetic mutation analysis revealed a mutation affecting the transactivation domain of the STAT3 gene. Conclusion. The hallmark of hyper IgE syndrome is serum IgE of >2000 IU/mL. Hyper IgE syndrome is a genetic disorder that is either autosomal dominant or recessive. A definite diagnosis can be made with genetic mutation analysis, and in this case, it revealed a very rare finding of the transactivation domain STAT3 mutation. Hyper IgE syndrome is a challenge for clinicians in establishing a diagnosis in suspected cases.